A new cryptic rock-dwelling Hemidactylus Oken, 1817 (Squamata: Gekkonidae) from northern Karnataka, India - Srinivasulu, Chelmala; Srinivasulu, Aditya; Kumar, Gandla Chethan (Zootaxa, 2018)
A new species of rupicolous gecko of the genus Hemidactylus is described from the Bellary District of Karnataka, India. The large-sized (SVL to at least 104.7 mm) gecko is characterized by the following suite of characters: dorsum with 16 longitudinal rows of irregularly arranged, subtrihedral, moderately to feebly keeled, striated tubercles at midbody; tail with transverse series of two enlarged tubercles on either side of the median furrow on the first and second tail segments each; 17–18 femoral pores on each side separated by 5 poreless scales. In conjunction, the molecular data based on concatenated analysis of nuclear (RAG-1 and PDC) and mitochondrial (Cytb) genes support the distinctiveness of the species and its affinities with large-bodied tuberculate Hemidactylus spp. from India and Sri Lanka, placing the new species basal to the entire H. prashadi group.